A computerized risk evaluation model for public-private partnership (PPP) projects and its application - Xu, Yelin; Lu, Yujie; P. C. Chan, Albert; J. Skibniewski, Miroslaw; F. Y. Yeung, John (International Journal of Strategic Property Management, 2012)
PPP projects usually involve more risks than other traditional procurement models because of their complexity. This paper presents the third stage of a funded study, which aims to develop a practical and computerized risk evaluation model for PPP projects. In the first and second stages, a risk hierarchal structure composed of 17 weighted risk factors is developed to describe risk profiles of PPP projects. The weightings and membership functions for risk factors are established using the Delphi survey technique and Fuzzy Set Theory. The risk evaluation model is then developed using a fuzzy synthetic evaluation approach. In the third stage, an automated decision support tool based on the risk evaluation model is designed for PPP practitioners by using Visual Basic for Application (VBA). The computerized tool can not only assist PPP participants to assess a PPP project’s overall risk level for auxiliary investment decision, but can also help practitioners to identify the most risky areas of a PPP project for effective risk response. To demonstrate the applicability of the computerized model, an illustrative case is finally provided. First Publish Online: 2 Oct 2012